Istanbul Gelisim University School of Foreign Languages: Monthly Bulletin (August 2023) - İstanbul Gelişim Üniversitesi Yabancı Diller Yüksekokulu (İstanbul Gelişim Üniversitesi / Istanbul Gelisim University, 2023)
Staying Motivated for Language Learning 1. Set Clear Goals: Define specific, achievable goals for your language learning journey. Whether it's being able to hold a conversation or watch a movie without subtitles, having clear goals can keep you focused. 2. Celebrate Small Wins: Acknowledge and celebrate your progress, even the small achievements. Each step forward is a step closer to your ultimate goal.
Keywords: Istanbul Gelisim University; School of Foreign Languages; Bulletins